Facile formation of colloidal silver nanoparticles using electrolysis technique and their antimicrobial activity - Lai, Chin Wei (Institution of Engineering and Technology, 2018)
In this research work, colloidal silver nanoparticles were successfully produced via an electrolysis method and their antibacterial activity was evaluated. This study aims to determine the optimum concentration of colloidal silver nanoparticles to produce an effective inhibition zone for Escherichia coli bacteria growth. Based on the results obtained, the applied current and reaction times during the electrolysis played a crucial role in determining the colloidal silver nanoparticles’ concentration (ppm). It was found that a minimum content of colloidal silver nanoparticles (0.02 ppm) was required to perform the 0.1 mm inhibition zone diameter on agar medium spread with E. coli bacteria. Interestingly, high concentrations of colloidal silver nanoparticles could exhibit high conductivity (µS/cm) as well as the high intensity of the maximum plasmon peak from the UV/vis absorption spectra at about 390 nm. In conclusion, this research work revealed the destruction of the cytoplasmic membrane and the rupture of the internal organisation of E. -coli bacteria, leading to the leakage of the cytoplasmic contents and cell death after having contact with sufficient concentration of colloidal silver nanoparticles.